PENERAPAN METODE DISKUSI KELOMPOK BERBASIS MEDIA VIDEO PEMBELAJARAN PADA MATA PELAJARAN PPKn KELAS VII A SMP NEGERI 19 MALANG. - Elvira, Fistra; Gultom, Andri Fransiskus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of a group discussion method utilizing instructional video media in the Pancasila and Civic Education (PPKn) subject for class VIIA at SMP Negeri 19 Malang. The research subjects were the PPKn teacher and the students of class VIIA at SMP Negeri 19 Malang. The primary issues identified during the learning process included low student engagement in discussion activities, a lack of confidence in expressing opinions, and instruction that remained teacher-dominated, preventing optimal learning interaction. This study employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation, and subsequently analyzed using the Miles and Huberman model, which encompasses data reduction, data display, and conclusion drawing. The results indicate that implementing the group discussion method supported by instructional video media fostered a more active, interactive, and collaborative learning environment. The use of video media helped students understand PPKn material in a more contextual manner, thereby encouraging them to actively participate in discussions, ask questions, express opinions, and collaborate within their groups. Furthermore, the teacher's role as a facilitator contributed to the creation of student-centered learning. Thus, the implementation of this group discussion method—supported by instructional video media—serves as an effective alternative for creating a more meaningful PPKn learning process that fosters active student engagement.